SOCIALLY RESPONSIBLE UNIVERSITY: PERSPECTIVES OF UNIVERSITY’S TOP MANAGEMENT LEADERS - Aida Suraya Md.Yunus; Norzaini Azman; Shukran Abdul Rahman (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2017)
Abstract Carnegie Foundation for Advancement of Teaching described UCE as the “collaboration between higher education institutions (HEIs) and their larger communities (local, regional or state, national, and global) for the mutually beneficial exchange of knowledge and resources in a context of partnership and reciprocity.” Thus the term socially responsible university was proposed by Teichler (2017) which refers to the need for a university to be relevant to the society and that “the university has to pay attention as well that it serves the generally agreed function of generating, preserving and disseminating knowledge appropriately.” However, this function is the least emphasized by the university community and in criteria for promotion. This Article examines the nature of and the factors affecting universities’ engagement with their communities from the multiple perspectives of top management leaders of the university. Specifically, the research sought to access views on UCE and explores cultural and institutional barriers to involvement, and levels of recognition, support, and reward for community engagement. The article highlights the two perspectives from the respondents; their beliefs of what is currently occurring in their universities and their views on what ought to be occurring. Abstrak Carnegie Foundation for Advancement of Teaching (Yayasan Carnegie untuk Kemajuan pengajaran) menggambarkan university-community engagement (UCE) sebagai